Emergence of continents above sea‐level influences sediment melt composition. (11th May 2021) - Liebmann, Janne; Spencer, Christopher J.; Kirkland, Christopher L.; E. Bucholz, Claire; He, Xiao‐Fang; Santosh, M.; Xia, Xiaoping P.; Martin, Laure; Evans, Noreen J.
Abstract: The Archean‐Proterozoic transition heralded a number of fundamental changes on Earth, including the oxygenation of the atmosphere, a marked emergence of continents above sea‐level, and an increase in δ 18 O of felsic magmas. The potential drivers for the latter are changes in the composition of supracrustal material or increased crustal reworking. Although the onset of subduction‐induced continental collision and associated enhanced crustal recycling could produce high‐δ 18 O felsic magmas, temporally constrained zircon δ 18 O reveals an increase in δ 18 O at ~2.35 Ga that predates the oldest widely recognized supercontinent. In this work, we use the O and Hf isotope ratios of magmatic zircon crystals in Archean and Proterozoic sediment‐derived granitoids of the North China Craton to track the incorporation of supracrustal material into magmas. The results are consistent with a Paleoproterozoic increase of continental freeboard producing sedimentary reservoirs with comparatively elevated δ 18 O that subsequently partially melted to generate the granitoids.